Grisly tales from Tumblewater - Vincent, Bruno, 1980-; Coates, Jo (London : Macmillan Children's Books, 2010)
Welcome to the shadowy district of Tumblewater, eternally rain-drenched, and home to a creepy collection of depraved characters, as newcomer Daniel Dorey is quick to discover.
Keywords: Storytelling -- Fiction; Orphans -- Fiction